Sufficiency as trend or tradition?—Uncovering business pathways to sufficiency through historical advertisements - Niessen, Laura; Bocken, Nancy M. P.; Dijk, Marc (Frontiers in Sustainability, 2023)
Climate change and dwindling resources underline that we need to bring production and consumption levels in line with planetary boundaries. Consumption, particularly in high-income communities, needs to be reduced and stabilized at sustainable levels. Businesses can play a key role as suppliers of goods and services and creators of demand. Some companies are rising to the challenge and promoting less consumption or “sufficiency” through long product lifetimes, repair services or rental offers, but they remain niche actors in the economic system. Similarly, while circular initiatives gain traction across sectors, firms focus primarily on recycling and efficiency improvements rather than supporting more radical ‘Reduce’ strategies. To engage companies in promoting sustainable levels of consumption, it can be helpful to understand pathways of established businesses who currently promote sufficiency. What can we learn from companies that currently promote sufficiency in their communications? Have they always advocated sufficient consumption, or have they changed recently? Through a historical perspective, we provide insights on the pathway of sufficiency for three companies. A document analysis of historical advertisements shines light on the messaging to potential customers over time. It is combined with an analysis of contemporary communications to connect the companies’ past and present sufficiency approaches. Understanding different pathways to sufficiency can help modern-day businesses to reconsider their own business models and orientation. It can also point out levers for policy to support a transformation towards sustainable and circular business models that promote living within planetary boundaries.